Die räumliche Differenzierung der Agrarlandschaft in der Arabischen Republik Jemen (Nordjemen) - Kopp, Horst (ERDKUNDE, 1975)
In hardly any other state in the world is the primary sector of the economy so important as in the Yemen Arab Republic. 80-90% of the employed population are employed in agriculture. Settled farmers in strong tribal organisations with a subsistence economy, irrigation practices dating back millenia and impressive terracing dominate the agrarian landscape even today. Relief and climate determine orographic differentiation which changes rapidly over small distances and there are also a number of varied ethnic and religious groups. The area of the country can be divided from west to east into eight large agrarian regions, largely determined by natural factors: coastal plain, great wadis, western mountains, central highlands, eastern mountains, semidesert, region of oases, desert. It is, however, only with a further sub division of these regions that it becomes possible to do mustice to the rich variety of the Yemenite agrarian landscape. Despite often large gaps in our knowledge, an attempt is made here to carry out such a subdivision taking anthropogeographical factors into account as well.